The Analysis of Time-Space Effect of Surrounding Rock Deformation of TBM Tunnels in Deep Composite Stratum with or without Support - Xiaoming Sun; Chao Ren; Junchao Yuan; Jianming Du; Jinshan Liu; Bo Guo (Advances in Civil Engineering)
In view of difficult problems such as excavation, segment simulation, deformation, and force measurement in the small-scale model testing of deep composite stratum TBM tunnel, the TBM simulation experimental device, the model segment ring prefabrication device, and the digital photogrammetry technology were comprehensively adopted. Also, the calculation methods were proposed. The analysis of the deformation characteristics as well as rupture of surrounding rock revealed those space-time effects: (1) When no support existed, the space-time effect of the surrounding rock deformation was concentrated in the following case: with the development of time, the deformation of surrounding rock starts from the sides of the arch waist at the junction of the composite stratum, while four arcs were derived and shear sliding occurred, resulting in overall collapse and destruction. (2) Following the support application, the space-time effect of the surrounding rock deformation was concentrated on the three stages of the interaction between the surrounding rock and the support, namely, the preliminary stage, the equilibrium process, and the instability state. The spatial effect was concentrated in the area where the surrounding rock was deformed and destroyed. The most severe area was the shallow surrounding rock, while the sub-violent area was the corner of the sidewall.